Impact of 1,2,4-thio-triazole derivative-based liniment on morphological and immunological blood parameters of dogs suffering from dermatomycoses - Hunchak, V. M.; Martynyshyn, V. P.; Gutyj, B. V.; Hunchak, A. V.; Stefanyshyn, O. M.; Parchenko, V. V.; Гунчак, В. М.; Мартинишин, В. П.; Гутий, Б. В.; Гунчак, А. В.; Стефанишин, О. М.; Парченко, Володимир Володимирович (My University, 2020)
The development of new preparations in soft medical form with antifungal effect and the ability to exert an antimicrobial effect on the secondary microflora accompanying the infection with accompanying desensitizing action is extremely relevant, as well as introduction of such drugs into veterinary medicine. The compound and compounding of the preparation with fungicidal and fungis-tatic effects for the treatment of dermatitides of dogs and cats caused by fungal skin infection are substantiated. The active agent of the developed medicine in the form of liniment was the S-derivative of triazole, and the base material was the standardized oil from milk thistle Silybum marianum. We determined the dynamics of the morphological parameters in blood of dogs with typical clinical skin pathology and its laboratory-confirmed fungal etiology. During the treatment of dogs with confirmed laboratory diagnosis “der-matophytosis”, the main medical preparation used was VetMikiDerm. It was heated on a water bath, gently applied and in thin layer was applied to the infected areas of skin 2–3 times a day over the period of treatment. Positive dynamics of recovery were seen al-ready at 3–4th days of the treatment (skin hyperaemia, itching and signs of inflammation reduced). On the 10–14th days of the treat-ment, the signs of regeneration of skin and recovery of the coat were observed. In all cases without exception (regardless of the area of skin infected by fungus) in this period, no fungi were microscopically found in the scrapes. Use of VetMikoDerm preparation during the course of the treatment, against the background of inhibition of the inflammatory processes, relief from itch and gradual recovery of the epidermis and hair, also contributed to the activation of the functional condition of the liver (the activity of amino transferases decreased, while the concentration of urea increased). Minimization of the negative effect of the products of fungal intox-ication, after use of the tested preparation for a medical purpose, led to recovery of the functional state of the cellular link of the im-munity. The treatment effect of the newly-developed preparation must be related to the active substance with notable fungicidal effect. Thio-triazole derivative exerts its medical effect by inhibiting sterol biosynthesis and contributes to the decrease in the content of ergosterol necessary for proliferation and growth of cells of fungus. The oil of milk thistle used as base material for liniment pro-vides not only high quality of medical form in the process of production and maintenance, and adds to the effect of the main sub-stance. Due to flavonoids, vitamins, carotenoids, milk thistle improves the condition of the skin, contributes to its active regeneration, stimulates reparation processes and recovery of the epidermis and the coat. Against the background of the effective fungicidal effect, the newly-developed VetMikoDerm preparation in the form of liniment exerted anti-inflammatory, hepatoprotective, immune-stimulating, wound-healing, regenerative and anti-itch effects.
Keywords: pharmacology; liniment; VetMikoDerm; Silybum marianum; dermatophytosis